Simulated CO(2)-induced ocean acidification for ocean in the East China: historical conditions since preindustrial time and future scenarios - Zhang, Han (Sci Rep, 2019)
Since preindustrial times, as atmospheric CO(2) concentration increases, the ocean continuously absorbs anthropogenic CO(2), reducing seawater pH and [Formula: see text] , which is termed ocean acidification. We perform Earth system model simulations to assess CO(2)-induced acidification for ocean in the East China, one of the most vulnerable areas to ocean acidification. By year 2017, ocean surface pH in the East China drops from the preindustrial level of 8.20 to 8.06, corresponding to a 35% rise in [H(+)], and reduction rate of pH becomes faster in the last two decades. Changes in surface seawater acidity largely result from CO(2)-induced changes in surface dissolved inorganic carbon (DIC), alkalinity (ALK), salinity and temperature, among which DIC plays the most important role. By year 2300, simulated reduction in sea surface [Formula: see text] is 13% under RCP2.6, contrasted to 72% under RCP8.5. Furthermore, simulated results show that CO(2)-induced warming acts to mitigate reductions in [Formula: see text] , but the individual effect of oceanic CO(2) uptake is much greater than the effect of CO(2)-induced warming on ocean acidification. Our study quantifies ocean acidification induced by anthropogenic CO(2), and indicates the potentially important role of accelerated CO(2) emissions in projections of future changes in biogeochemistry and ecosystem of ocean in the East China.